Analisis Faktor-faktor yang Mempengaruhi Tingkat Kedisiplinan Kerja Pegawai pada Kantor Sekretariat Daerah Kota Pontianak - Mujakar Mujakar; Yusmainiar Yusmainiar (Jurnal Ilmiah Aset, 2018)
The purpose of this research is to determine the factors that affect the level of discipline of work employees at the Secretariat of the regional city of Pontianak. The number of samples as many as 70 people. The data collected through questionnaire and analyzed by multiple Linear regression analysis technique. The result showed that variable goals and capabilities, exemplary leadership, retribution, justice, waskat, legal sanctions and humanitarian has an positive influence against the level of discipline of employees at the Secretariat of the city areas Pontianak.